Assessment of Helminthosporium blight resistance in barley using disease stress tolerance Index - SRIKANTA DAS, NITAI MUDI, SUNITA MAHAPATRA* and (Indian Phytopathology, 2016)
Disease stress tolerance index was found suitable selection criteria for assessing the barley lines for their higher disease stress tolerance and yield potential. The genotypes K 824, K 832, RD 2035, Jyoti and K 826 performed with uniform superiority in both disease stress free and disease stress environment. Potential yield under control environment was positively correlated with yield under disease stress environment, mean productivity, disease tolerance, geometric mean productivity and disease stress tolerance index in both the years of the experiment.